O ditongo nasal tônico -ão falado por ítalo-descendentes de Santa Maria do Engano/ES : uma análise sociolinguística - Meneghel, Sílvia Ângela Pícoli (2015)
The state of Espírito Santo received thousands of Italian immigrants in the last twenty-five years of the nineteenth century. The presence of these immigrants and the language contact from there emerged have left marks on the language spoken by descendants today, specifically where the two linguistic systems differ from each other. Thus, this study seeks to describe the variation in the pronunciation of the nasal diphthong tonic –ão into the speech of the descendants of Italian immigrants from the community of Santa Maria do Engano in Alfredo Chaves, Espírito Santo. Bearing in mind the importance of analyzing a linguistic phenomenon linking it to its social context, in addition to the peculiarities of our object of study, we take as theoretical framework in this research the Sociolinguistics, specifically the Theory of Variation and Change Linguistics, but also considering themes concerning Language Contact. We support even in phonetics and phonology studies. Our corpus consisted of 40 sociolinguistic interviews with residents of Santa Maria do Engano, from which we obtained 1956 data. The Goldvarb X Program (SANKOFF, TAGLIAMONTE and SMITH, 2005) selected as significant the social variables age, education level and sex, and as linguistic variables, the extension of the term and the preceding and following contexts of the diphthong. Our results, considering the pronunciation of the nasal diphthong tonic -ão with the Venetian influence, pointed as favoring factors: a) words with more than one syllable; b) subsequent consonant on the previous preceding context; c) the pause, for the following context; and d) the elderly informants, male and with low educational level.